The Vietnam War : a controversial conflict - Orr, Tamra (World history (Lucent Press), 2020)
Details the struggles and events that led up to the Vietnam War and examines the United States' role in the conflict, including how the war affected American history and morale for years to come. Includes extensive photographs, a timeline, sources for further information, and an index.